Kewenangan Pemerintah Daerah Dalam Pengelolaan Pertambangan Mineral Batubara - Baura, Lineke; Saptenno, Marthinus Johanes; Pietersz, Jemmy Jeffrey (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2022)
Introduction: Based on Act Number 4 of 2009 and Act Number 23 of 2014, Local Governments have authority in the management of minerals and coal mining. But with the determined by Act Number 3 of 2020, domination of minerals dan coals mining is held by Central Government. Purposes of the Research: For this reason, it is necessary to review the constitutional right and authority of Local Goverment to held minerals and coals mining. Methods of the Research: The type of research used in this study is a normative juridical research that is descriptive analytical by using statute approach and conceptual approach. Sources of legal materials are primary legal materials, secondary legal materials and tertiary legal materials through literature studies. Results of the Research: Based on the results of the study, minerals and coals mining is one of government affairs that is distributed to Local Government in accordance with Act Number 3 of 2020. The authority cannot be removed by the regulations contained of Act No. 3 of 2020. This is contrary to Local Government’s constitutional rights and The 1945 Constitution of State of Republic of Indonesia.